Penggantian Direksi oleh Pemegang Saham Baru Setelah Akuisisi Berdasarkan Undang Undang Perseroan Terbatas - Suwinto Johan; Dativa Averina Santie (Hang Tuah Law Journal, 2022)
The dismissal or replacement of a company's board of directors has become a frequently discussed thing in the business world. A new shareholder replaces the board of directors or the shareholder rejects the board of directors' accountability report as a reason for the replacement of the board of directors. The Board of Directors is an important part of a company. This study aims to discuss the position of directors, the process of dismissal or replacement of directors, and compensation due to directors been replaced. This study uses a normative juridical method. This study concluded that the directors are organs of the company not workers in the company. The relationship between directors and companies is based on the Limited Liability Company Law, the Capital Market Law, and the Anti-Monopoly and Business Competition Law. This relationship does not refer to the Labor Act. The position and process of replacing the board of directors based on the Limited Liability Company Law. Fired directors may receive compensation as stipulated in the agreement between the board of directors and the company. The Company can be represented by the board of commissioners as agreed in the General Meeting of Shareholders.